Pengaruh Pembelajaran Daring dengan Model Mind Mapping Berbasis Digital Android terhadap Hasil Belajar Mahasiswa PGSD UNDANA - Sarah Nurhabibah; Paulina Riwu Ga; Taty R. Koroh; Treesly Adoe; Netty E. A. Nawa (Universitas Nusa Cendana, 2021)
This study aims to determine the effect of online learning with an Android-based digital mind mapping model on the learning outcomes of UNDANA PGSD students. Quantitative method was used in this study with a one-group pretest-posttest design. Hypothesis testing of cognitive learning outcomes using the T test with the help of the SPSS 22 program. The results showed that there was an effect of applying the Android-based digital mind mapping model to the cognitive domain learning outcomes of 6th semester PGSD UNDANA students, because the value of sig 2 tailed 0.000 < 0.05 then there was the difference in values before and after learning is carried out using a digital android-based mind mapping model (the android-based digital mind mapping model applied by the lecturer was successful).